NTS2-selective neurotensin mimetics with tetrahydrofuran amino acids. Issue 1 (1st January 2017) - Simeth, Nadja A.; Bause, Manuel; Dobmeier, Michael; Kling, Ralf C.; Lachmann, Daniel; Hübner, Harald; Einsiedel, Jürgen; Gmeiner, Peter; König, Burkhard
Graphical abstract: Abstract: Stimulation of the NTS2 neurotensin receptor causes antipsychotic effects and leads to a promotion of the μ-opioid-independent antinociception, which is important in the modulation of tonic pain sensitivity. We report the synthesis and properties of a small library of peptidic agonists based on the active neurotensin fragment NT(8–13). Two tetrahydrofuran amino acid derivatives were synthesized to replace Tyr 11 in NT(8–13). Additionally, Arg 8, Arg 9, and Ile 12 of the lead peptide were exchanged by Lys, Lys, and Gly, respectively. The new compounds showed substantial NTS2 binding affinity and up to 1000-fold selectivity over NTS1. The highest selectivity ( K i (NTS2): 29 nM, K i (NTS1): 35, 000 nM) was observed for the peptide analog17 R trans .